Information technology. Computer graphics. Graphical Kernel System for three dimensions (GKS-3D) language bindings. Information technology. Computer graphics. Graphical Kernel System for three dimensions (GKS-3D) language bindings. C Part 4, (1st April 1992) - British Standards Institution,
No abstract available